Students’ Attitudes Toward English Writing Activities at SMP Negeri 29 Medan - Novita Novita; Yeni Erlita (TRANSFORM : Journal of English Language Teaching and Learning, 2023)
This study aimed to analyze the students’ attitudes toward English writing activities. The method of this study was descriptive qualitative by conducting the in-depth interview and questionnaire sheets. The data of this study were transcription of the students’ attitudes toward English writing activities especially in recount text topic. Moreover, the data sources were 31 students at grade 8 of SMP Negeri 29 Medan. The results showed that the dominant components of students’ attitudes in English writing activities was affective component (60,75%), followed by conative component (58,06%) and cognitive component (54,8%) which could be interpreted that the students had positive attitude regarding to the writing of recount text. It was reflected from three components. For cognitive component, the students believed that their writing skills will be better after studying the material despite the many difficulties encountered when writing recount text. For affective component, the students felt happy, interested and really enjoyed the lesson. And for conative component, the students were able to pay attention during teacher explained about material, asked questions about material that has been understood and always discussed it with friends. So that, this indicated that their overall attitude was positive.